Refined Opium Extract (Shireh) Poisoning: A 10-Year Retrospective Study in a Referral Poison Control Centre in Iran - Marzieh Azarakhsh; Mitra Rahimi; Nasim Zamani; Sepideh Arbabi (Asia Pacific Journal of Medical Toxicology, 2021)
Background: There is limited data on refined opium extract (Shireh) abuse, especially the magnitude of its complications and its mortality rates. To bridge such a gap, in this study, we aimed to investigate the frequency of pure refined opium extract poisoning and its consequences in a sample of our patients. Methods:This retrospective study was conducted on all the patients presented to our center with pure refined opium extract poisoning. Patients’ demographics, clinical and laboratory data, and outcome were collected during a ten-year period between 2006 and 2016. The included patients were divided into two groups: those who remained conscious and those who developed loss of consciousness. However, they were compared subsequently. Results:A total of 227 patients were evaluated. Most (75.8 %) of them were male. Mean age was 38.26±25.91 years. We found a significant correlation between educational (.038), marital (<.001), and occupational status (<.001) and age-gender groups of the patients. The mean amount of refined opium extract consumed was 4400 mg which had significant correlation with hospitalization period (<.001) and on-arrival rhabdomyolysis (<.001). We also found a correlation in vomiting (<.001), dizziness (.015), respiratory distress (.001), and apnea (<.001) between the two groups. The mean hospitalization period was 2.3 days and the mortality rate was 1.76%. Conclusion: Naloxone therapy use effective in most cases of pure poisoning with refined opium extract. There were four deaths incidences three of which happened due to cardiopulmonary arrest following body packing. Further studies in this type of poisoning are recommended.